Metaphors are like lenses: Electrophysiological correlates of novel meaning processing in bilingualism - Jankowiak, Katarzyna; Naranowicz, Marcin; Rataj, Karolina (SAGE Publishing, 2021)
Aims and objectives: The study provides new insights into how bilingual speakers process semantically complex novel meanings in their native (L1) and non-native language (L2). Methodology: The study employs an EEG method with a semantic decision task to novel nominal metaphors, novel similes, as well as literal and anomalous sentences presented in participants’ L1 and L2. Data and analysis: In total, 29 native speakers of Polish (L1) who were highly proficient in English (L2) took part in the study. The collected EEG signal was analyzed in terms of an eventrelated potential analysis. The statistical analyses were based on behavioral data (reaction times and accuracy rates) as well as mean amplitudes for the four conditions in the two languages within the N400 and LPC time windows. Findings: The results revealed the N400 effect of utterance type modulated by language nativeness, where the brainwaves for anomalous sentences, novel nominal metaphors, and novel similes converged in L2, while in L1 a graded effect was observed from anomalous sentences to novel nominal metaphors, novel similes and literal sentences. In contrast, within the late time window, a more pronounced sustained negativity to novel nominal metaphors than novel similes was observed in both languages, thus indicating that meaning integration mechanisms might be of similar automaticity in L1 and L2 when bilingual speakers are highly proficient in their L2. Altogether, the present results point to a more taxing mechanisms involved in lexico-semantic access in L2 than L1, yet such an increased effort seems to be resolved within the meaning integration phase. Originality: The findings present novel insights into how bilinguals construct new unfamiliar meanings and show how and when cognitive mechanisms engaged in this process are modulated by language nativeness. Significance: The study might provide crucial implications for further research on bilingual semantic processing as well as human creativity
Keywords: novel meaning creation; nominal metaphor; simile; bilingualism; N400; sustained negativity